Prostatic carcinoma metastatic to the optic nerve - Cerovski, Branimir (Array, 2009)
Abstract: Optic nerve can be infiltrated with various tumors and inflammatory processes, with a considerable prevalence of primary over secondary tumors. Metastases of gastric carcinoma to the optic nerve are less frequently, and those of prostatic carcinoma very infrequently observed. A 66 year-old man presented with metastasis to the optic nerve with consequential vision loss to the level of light perception developed two years after prostatic surgery. Systemic therapy with methylprednisolone resulted in a satisfactory vision function recovery. According to literature data, prostatic carcinoma metastases to the optic nerve occur very rarely. In our patient with the optic nerve infiltration found on the first clinical examination, papillary edema was associated with the signs of optic nerve functional impairment (visual acuity, visual field, unilateral RAPD). An infiltrative process involving a distal portion of the optic nerve usually does not cause papillary alterations, and produces a clinical picture of retrobulbar optic neuropathy, such as that observed in our patient on the second clinical examination, showing the signs of optic nerve damage